Dependence of the AE maximum burst amplitude on the deformation mechanism in some rocks - A. M. JAROSZEWSKA (Archives of Acoustics)
Maximum amplitude of acoustic emission events in 10 second intervals were measured in the samples of dolomite and sandstone under uniaxial compressive load. The observed sudden increase of the maximum amplitude, in a function of load, indicates the beginning of the unstable propagation of microfractures, leading to uncontrolled failure of a sample. The maximum amplitude dependence on load, as directly related to the AE source mechanism, can be used in prediction of the rock damage in situ.